Screening science, producing the nation: popular science programs on Israeli television (1968–88). - Katz-Kimchi, Merav (Media, Culture & Society, 2012)
From 1968 on, the state of Israel deployed television as a tool in the service of its ongoing project of reproducing the nation and as a propaganda tool that targeted the population of the newly occupied territories and the Palestinian Arab citizens of Israel. With the collaboration of the scientific elite, the televising of original popular science programs, aired on the sole government-controlled channel at prime time, contributed immensely to these projects. Through these programs, the state disseminated a specific image of the nation’s scientific prowess for popular consumption in the euphoric aftermath of the Six Day War. This article examines the first 20 years of the state’s projects, during which the grip of Zionist collectivism was still strong, the monopoly of the government-controlled channel was not yet challenged, and the programs enjoyed astonishingly high ratings. My examination focuses on the ideology and motivations of the producers; the ways in which the communication elite and the scientific elite, enjoying a position of hegemony, collaborated by disseminating the nation’s accomplishments in both the Arabic and Hebrew programs; and the actual content of the programs at large and specifically that of four episodes of Tazpit, the popular science program of the 1980s.